Zur Quantifizierung von Reurbanisierungstendenzen - Matthes, Gesa (Raumforschung und Raumordnung | Spatial Research and Planning, 2014)
This paper deals with spatial processes of demographic change in the city and the region of Hamburg by using official statistics. It aims to answer the questions if there is a stable (re)concentration of population in transport-reducing settlement structures, i.e. functionally mixed quarters that are easily accessible by public transport, and if a new preference for living in cities can be observed. Knowing that it is actually possible to measure reurbanization in Hamburg applying common concepts, the paper analyses patterns of migration in a more detailed way. This reveals that the growing population within the city and the concentration of population in the core mainly result from two developments: inter-regional migration grows (mainly from other cities into the core) and the cityʼs residents move less often to the outskirts. The inner-regional processes of population change result from a changed migration behavior of persons over the age of 30 as well as children and cohort effects of the over 45-year-olds, whereas a changed behavior of young professionals and students (18- to 29-year-olds) causes the growing inter-regional exchange. The findings support existing theses regarding the reasons for reurbanization. Notably the thesis that the group of aged persons supports reurbanization can be observed in the quantitative data.